Patterns of Spatial Transformation in Traditional Houses of Bayung Gede Village, Bali - Mulya Wahyu Rukmana; Dwita Hadi Rahmi; Dimas Wihardyanto (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
This study aims to identify the patterns and levels of spatial transformation in traditional houses in Bayung Gede Village, Bali, and to understand the transformation process within the social, cultural, and spatial cosmological context of the Bali Aga community. The research employs a descriptive qualitative approach using a case study method, incorporating field observations, interviews, and plan reconstructions of six purposively selected house samples. The results indicate that spatial transformations can be classified into four main patterns: the addition of utility spaces, the expansion of domestic spaces, the transformation of spatial functions, and the adaptation of activity spaces. Furthermore, based on the level of intervention, the transformations are categorized into three levels: minor, moderate, and major. An analysis based on the Hulu–Teben concept reveals that spatial changes predominantly occur in the teben zone, which is profane and more flexible, while the hulu zone, which holds sacred values, remains preserved. This finding suggests that spatial transformations occur selectively and gradually without eliminating the fundamental structure and cosmological values of traditional spatial organization. Therefore, traditional houses in Bayung Gede Village demonstrate an adaptive capacity in responding to modern needs while maintaining their vernacular architectural identity.